Analisis Semiotika pada Sampul Majalah National Geographic - Wulandari, Wulandari (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2018)
Our planet become damaged, every year more garbage we made. Many activist aware us about environment, they do campaign. National Geographic, one of magazine that aware about environment has issues they cover about waste that damaging the Iceland. They represented with digital process into a photo. This time, the photo told to us, that one day our planet really become a plastic. This cover has bring pro and contra, because the idea same with the campaign of Tesco eco bag. The idea has rebuild, this is what we called imitation. in everything of figure there are two messages, first as denotative and second as connotative. As we know the National Geographis bring us about that messages to people, that environment very important.